Dispersion method of silicon nanowires, prepared dispersed powder and application

Through the combination of chemical dispersed coating agent and conductive agent, combined with high-speed stirring and spray granulation technology, the aggregation problem of spongy silicon nanowires is solved, and its efficient dispersion and excellent electrical properties are achieved.

CN119240704APending Publication Date: 2025-01-03TOMI CHENGDU APPLIED TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310771192.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art is difficult to effectively disperse spongy silicon nanowires, resulting in serious agglomeration and affecting their subsequent processing and application.

Method used

Using a combination of chemical dispersed coating agent and conductive agent, through high-speed stirring and physical dispersion method of ball milling or sanding, combined with centrifugal spray granulation technology, dispersed powder with a cladding layer is formed to prevent intermolecular forces and electrostatic effects. Aggregation caused by bonding in the air.

Benefits of technology

It achieves excellent dispersion effect of silicon nanowires, improves its electrical performance and cycle life, and lays a solid foundation for subsequent processing and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240704A_ABST
    Figure CN119240704A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of nano material preparation. The invention provides a dispersion method of silicon nanowires, prepared dispersed powder and application, and the dispersion method comprises the following steps: uniformly stirring and mixing a dispersion coating agent, a solvent, the silicon nanowires and a conductive agent, crushing, and carrying out spray granulation on the obtained slurry to obtain the dispersed powder of the silicon nanowires. According to the preparation method, a chemical dispersion coating agent is added, spongy silicon nanowire blocks can be preliminarily dispersed into slurry through physical dispersion of high-speed stirring, fine dispersion is performed through physical crushing dispersion modes such as further ball milling or sand milling, and finally, the spongy silicon nanowire particles are prepared through a centrifugal spray granulation mode. And finally, silicon nanowire particles with a coating layer and good dispersion are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano material preparation, and relates to a silicon nanowire dispersion method, a prepared dispersion powder and an application thereof. Background Art

[0002] At present, one-dimensional silicon nanowires have the inherent high mass specific capacity characteristics of silicon-based anode materials. Compared with other silicon-based anode materials, such as silicon nanoparticles, nano-silicon oxide anode (SiO x ), etc. It also has the characteristics of small volume change and high initial charge and discharge efficiency, and is an ideal material for the new generation of silicon-based negative electrodes.

[0003] Silicon nanowires grown by the VLS method (vapor-liquid-solid method) have a microscopic diameter of less than 250nm and a length of millimeters. Their macroscopic state is entangled sponge clumps. Compared with silicon nanoparticles and nano-silicon oxide particles, which have good processing performance in the subsequent modification process, sponge-cluster silicon nanowires are difficult to be directly applied to subsequent processing. The prepared sponge-cluster silicon nanowires must first be dispersed to form granular fine powders before subsequent modification processing can be carried out.

[0004] Since the primary particles of silicon nanowires are one-dimensional linear structures below 250nm, they have a huge surface area and thus have small size effect, macro quantum tunneling effect, surface effect, etc., which causes serious agglomeration of silicon nanowires during the dispersion process.

[0005] There are three main reasons for the agglomeration of silicon nanowires: agglomeration caused by intermolecular forces, agglomeration caused by electrostatic forces, and adhesion in the air.

[0006] Agglomeration caused by intermolecular forces of silicon nanowires: The distance between silicon nanowires is extremely short, and the van der Waals force between particles is much greater than the gravity of the particles themselves, causing the silicon nanowires to attract each other and agglomerate; the silicon-hydrogen bonds, adsorbed wet bridges and other chemical bonds on the surface of silicon nanowires can also easily cause the particles to adhere to each other and aggregate.

[0007] Electrostatic force of silicon nanowires causes agglomeration: During the dispersion process of silicon nanowires, due to impact, friction and length reduction, a large amount of positive or negative charges are accumulated on the surface of the newly formed silicon nanowires. Some of these particles have positive charges on their surfaces, while others have negative charges. These charged particles are extremely unstable. In order to become stable, they attract each other, contact and connect with each other, and agglomerate.

[0008] Adhesion of silicon nanowires in the air: When the relative humidity of the air exceeds 65%, water vapor begins to condense on the surface of silicon nanowires and between particles, and the agglomeration effect is greatly enhanced due to the formation of liquid bridges between particles; in addition, a large amount of mechanical energy or thermal energy is absorbed during the dispersion process of silicon nanowires, so that the surface of the newly formed ultrafine particles has a very high surface energy, and the silicon nanowire particles are in an extremely unstable state. In order to reduce the surface energy, they often reach a stable state by agglomerating and approaching each other, which is also easy to cause agglomeration between silicon nanowires.

[0009] Therefore, the dispersion of silicon nanowires requires solving the problems of intermolecular force agglomeration, electrostatic force agglomeration, and bonding agglomeration in the air, so as to obtain a uniformly dispersed micron-sized powder material.

[0010] Generally, the dispersion methods of nanomaterials are divided into physical dispersion and chemical dispersion.

[0011] Physical dispersion includes three dispersion methods: mechanical dispersion, ultrasonic dispersion, and high energy treatment:

[0012] Mechanical dispersion is a method of dispersing nanoparticles in a medium by using mechanical energy such as external shear force or impact force. It is a very complex dispersion process. It is achieved by applying mechanical force to the dispersion system, causing changes in the physical and chemical properties of the substances in the system and a series of chemical reactions. This phenomenon is called mechanochemical reaction. Mechanical dispersion methods include grinding dispersion, ordinary ball milling, sand milling dispersion, vibration ball milling, sand milling dispersion, colloid milling dispersion, air milling dispersion, mechanical high-speed stirring, etc.

[0013] Ultrasonic dispersion is an effective method to reduce the agglomeration of nanoparticles. The local high temperature, high pressure or strong shock wave and micro jet generated by ultrasonic cavitation can significantly weaken the nano-interaction energy between nanoparticles, effectively prevent the agglomeration of nanoparticles and make them fully dispersed. However, overheated ultrasonic stirring should be avoided because with the increase of thermal energy and mechanical energy, the probability of particle collision also increases, which leads to further agglomeration. Therefore, the minimum ultrasonic dispersion method should be selected to disperse nanoparticles.

[0014] High-energy treatment is to generate active points on the surface of nanoparticles through the action of high-energy particles, increase surface activity, make it easy to react or adhere to other substances, and modify the surface of nanoparticles to achieve the purpose of easy dispersion. High-energy particles include corona, ultraviolet rays, microwaves, plasma rays, etc., which stimulate the surface of nanoparticles to generate active points.

[0015] Chemical dispersion includes two dispersion methods: surface chemical modification and dispersion using dispersants.

[0016] Surface chemical modification is to change the surface structure and state of nanoparticles through chemical reaction between the surface of nanoparticles and the treatment agent to achieve the purpose of surface modification, which is called surface chemical modification of nanoparticles. Surface chemical modification includes three dispersion methods: coupling agent method, esterification reaction, and surface grafting modification.

[0017] The use of dispersants to disperse mainly changes the surface charge distribution of particles through dispersant adsorption, producing electrostatic stabilization and steric stabilization to achieve the dispersion effect. There are three main mechanisms: electrostatic stabilization mechanism, steric stabilization mechanism, and electro-steric hurdle dispersion mechanism.

[0018] Silicon-based negative electrode materials, such as silicon nanoparticles, are commonly dispersed by grinding micron silicon powder into nanopowders of the required size through dry high-energy ball milling. There is also a gas phase chemical reaction method (CVD method) to directly prepare nano-scale silicon powder from gaseous silane.

[0019] Since the dispersion of silicon nanowires is more difficult, the above-mentioned corresponding problems need to be solved. At present, there is still a lack of a new technical solution for effectively dispersing silicon nanowires, especially silicon nanowires that have formed sponge clumps, to obtain ideal dispersed materials. Summary of the invention

[0020] In view of the problems existing in the prior art, the present invention provides a silicon nanowire dispersion method, a prepared dispersion powder and an application. The dispersion method comprises stirring and mixing a dispersion coating agent, a solvent, a silicon nanowire and a conductive agent, crushing them, and then spraying and granulating the obtained slurry to obtain a silicon nanowire dispersion powder. The present invention adopts the addition of a chemical dispersion coating agent, and firstly disperses the sponge-like silicon nanowire block into a slurry by physical dispersion with high-speed stirring, and then finely disperses it by further physical crushing and dispersion methods such as ball milling or sand milling, and finally obtains silicon nanowire particles with a coating layer and good dispersion by centrifugal spray granulation.

[0021] To achieve this object, the present invention adopts the following technical solutions:

[0022] In a first aspect, the present invention provides a method for dispersing silicon nanowires, the method comprising the following steps:

[0023] The dispersion coating agent, solvent, silicon nanowires and conductive agent are mixed and crushed, and the crushed slurry is spray-granulated to obtain dispersed powder of silicon nanowires.

[0024] The present invention adopts the method of adding a chemical dispersing coating agent and physically dispersing by high-speed stirring to initially disperse the sponge-like silicon nanowire (SiNWs) block into a slurry, and then finely disperses it by further physical dispersion of ball milling or sand milling, and finally obtains silicon nanowire particles with a coating layer and good dispersion by centrifugal spray granulation.

[0025] Among them, the dispersing coating agent of the present invention is preferably PVDF, PMMA, PDMS or PI-PA copolymer, etc., which can fully disperse the entangled and agglomerated SiNWs, and in the spray drying process, the dispersing coating agent can be used as a polymer coating agent to play a coating role, and can form a dense perfect coating on the surface of the dispersed nano-scale SiNWs, prevent the oxidation of the SiNWs surface under high temperature, improve the initial charge and discharge efficiency of the SiNWs material, and effectively block the intermolecular forces between silicon nanowires, prevent the generation of liquid bridges, and prevent agglomeration.

[0026] Since nano-sized SiNWs are more likely to react with water or water vapor, it will cause SiNW S The material capacity and the first charge and discharge efficiency are reduced. Therefore, when the dispersed coating agent is also used as a polymer coating agent, the perfect coating layer formed on the surface of the silicon nanowire can avoid the reaction between nano-scale SiNWs and water, thereby improving the first charge and discharge efficiency of the silicon nanowire.

[0027] On the other hand, the dense coating formed on the surface of silicon nanowires can effectively buffer the volume change caused by the expansion and contraction of the silicon nanowires during the charge and discharge cycle, slow down the formation of new SEI layer, and thus extend the cycle life of silicon nanowires.

[0028] In addition, the present invention also adds a conductive agent with good conductivity (such as carbon nanotubes CNTs, vapor-grown carbon fibers VGCF, graphene, etc.). On the one hand, it can improve the overall conductivity of the material and reduce impedance. On the other hand, it mainly utilizes its anti-static function to avoid agglomeration between silicon nanowires caused by static electricity.

[0029] The solvent of the present invention preferably uses NMP (N-methylpyrrolidone), DMSO (dimethyl sulfoxide), DMAC (dimethylacetamide), DMF (N,N-dimethylformamide), TEP (triethyl phosphate), and THF (tetrahydrofuran) as solvents, which can avoid the negative impact of moisture on the electrical properties of SiNWs, thereby effectively maintaining the excellent performance of high capacity and high first efficiency of SiNWs.

[0030] The present invention adopts a multi-stage dispersion technology, that is, a vacuum mechanical stirring method is selected to break up the tangled silicon nanowires into a small amount of agglomerated silicon nanowires. However, considering that it is difficult to cut silicon nanowires with a length of millimeters into silicon nanowires of tens of microns, it is necessary to break the longer silicon nanowires into silicon nanowires with a length of less than 20μm by ball milling or sand milling.

[0031] The present invention forms powder by spray granulation: the silicon nanowire slurry is quickly sprayed and atomized to obtain spherical, quasi-spherical and short-wire particles with good fluidity, and the intermolecular forces between nano-scale silicon nanowires are isolated from time and space, making agglomeration impossible; the dried dispersion coating agent PVDF, PMMA, PDMS, PI-PA copolymer, etc. also serves as a polymer coating agent, has moisture absorption resistance, and can effectively prevent the silicon nanowires from agglomerating due to the formation of liquid bridges by absorbing moisture;

[0032] Therefore, the present invention can effectively solve the problems of intermolecular force agglomeration, electrostatic force agglomeration and bonding agglomeration in the air between silicon nanowires through the dispersion method, obtain dispersed powder with excellent dispersion effect, and make the dispersed and coated silicon nanowires have excellent electrical properties, laying a solid foundation for the subsequent processing and application of silicon nanowires.

[0033] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0034] As a preferred technical solution of the present invention, the dispersed coating agent includes any one of PVDF (polyvinylidene fluoride), PMMA (polymethyl methacrylate), PDMS (polydimethylsiloxane) or PI-PA copolymer or a combination of at least two thereof, and typical but non-limiting examples of the combination include a combination of PVDF and PMMA, a combination of PVDF and PDMS, a combination of PVDF and PI-PA copolymer, a combination of PMMA and PDMS, a combination of PMMA and PI-PA copolymer, or a combination of PDMS and PI-PA copolymer.

[0035] Preferably, the conductive agent includes any one of CNTs, VGCF or graphene, or a combination of at least two of them. Typical non-limiting examples of the combination include a combination of CNTs and VGCF, a combination of CNTs and graphene, or a combination of VGCF and graphene.

[0036] Preferably, the solvent comprises any one or a combination of at least two of NMP, DMSO, DMAC, DME, DMF, TCM, TEP or THF, typical but non-limiting examples of the combination include a combination of NMP and DMSO, a combination of NMP and DMAC, a combination of NMP and DMF, a combination of NMP and TCM, a combination of TEP and THF, or a combination of DMF and DMSO.

[0037] Preferably, the silicon nanowires include silicon nanowires prepared using a VLS method.

[0038] Preferably, the diameter of the silicon nanowire is ≤250 nm, such as 250 nm, 200 nm, 150 nm, 100 nm or 50 nm, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0039] Preferably, the silicon nanowires are in the form of a sponge-like entangled bulk solid.

[0040] As a preferred technical solution of the present invention, based on the total mass of the dispersing coating agent, the silicon nanowires and the conductive agent being 100wt%, the dispersing coating agent accounts for 0.1 to 8wt%, for example, 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt% or 8wt%, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0041] Preferably, based on the total mass of the dispersed coating agent, the silicon nanowires and the conductive agent being 100wt%, the silicon nanowires account for 87-99.8wt%, for example, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5% or 99.8%, etc., but are not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0042] Preferably, based on the total mass of the dispersed coating agent, the silicon nanowires and the conductive agent being 100wt%, the conductive agent accounts for 0.1-5wt%, for example, 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0043] In the present invention, if the amount or proportion of the dispersing coating agent is too much, it will be difficult to disperse and the impedance of the obtained coated powder will be too high, thereby reducing the electrical properties of the material. If the amount of the dispersing coating agent is too little, it will be difficult to form a complete coating layer on the surface of the material, resulting in poor dispersion and coating effects.

[0044] In the present invention, when the amount of the conductive agent is too high, the cost will increase and the energy density of the material will be reduced; when the amount is too low, the conductivity of the material coating layer will be reduced, thereby reducing the dispersion effect.

[0045] Preferably, after the dispersion coating agent, solvent, silicon nanowires and conductive agent are uniformly mixed, the solid content of the system is 0.5-10wt%, for example, 0.5wt%, 0.7wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt% or 10wt%, etc., but are not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0046] In the present invention, when the solid content of the obtained slurry is too high, it is difficult to fully disperse into a uniform and stable dispersion, resulting in difficulty in subsequent spray drying; when the solid content of the slurry is too low, the spray drying efficiency is reduced.

[0047] As a preferred technical solution of the present invention, the dispersion coating agent and the solvent are firstly mixed evenly, and then the silicon nanowires and the conductive agent are added and stirred evenly.

[0048] Preferably, the mixing is carried out in a double planetary vacuum mixer.

[0049] Preferably, the mixed vacuum degree is -0.01 to -0.098 MPa, for example, -0.098 MPa, -0.09 MPa, -0.08 MPa, -0.07 MPa, -0.06 MPa, -0.05 MPa, -0.04 MPa, -0.03 MPa, -0.02 MPa or -0.01 MPa, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0050] Preferably, the mixing rotation speed is 1000-5000 rpm, for example 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm or 5000 rpm, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0051] Preferably, the mixing time is 60 to 180 min, for example 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min or 180 min, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0052] As a preferred technical solution of the present invention, the vacuum degree of stirring is -0.01 to -0.098 MPa, for example, -0.098 MPa, -0.09 MPa, -0.08 MPa, -0.07 MPa, -0.06 MPa, -0.05 MPa, -0.04 MPa, -0.03 MPa, -0.02 MPa, -0.01 MPa, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0053] The present invention preferably performs mixing and stirring under vacuum. Silicon wires with a huge surface area will absorb a large amount of air to form a three-phase mixture of gas, liquid and solid, and the dispersion effect will be very poor. However, performing the mixing and stirring under vacuum can greatly improve the effects of dispersion, stirring and mixing, and the lower the vacuum degree, the better the dispersion effect.

[0054] Preferably, the stirring speed is 1000-5000 rpm, for example 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm or 5000 rpm, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0055] Preferably, the stirring time is 60 to 180 min, for example, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min or 180 min, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0056] As a preferred technical solution of the present invention, the crushing method includes ball milling or sand milling.

[0057] Preferably, the ball-to-material ratio of the ball mill or sand mill is (2.5-4):1, for example 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1 or 4:1, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0058] Preferably, the grinding balls for ball milling or sand milling include zirconium balls and / or corundum balls.

[0059] Preferably, the grinding balls of the ball mill or sand mill include at least two diameters.

[0060] Preferably, the mass ratio of the grinding balls of the ball mill is:

[0061] Φ1:Φ3:Φ5:Φ8:Φ10=(10~30):(20~40):(25~35):(5~15):(3~15), for example, it can be 10:20:25:5:3, 15:25:30:8:9, 20:30:30:10:8, 25:28:32:12:10 or 30:40:35:15:15, etc., but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0062] Preferably, the rotation speed of the ball mill or sand mill is 300-1500 rpm, for example 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm or 1500 rpm, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0063] Preferably, the ball milling or sand milling time is 10 to 90 min, for example 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0064] Preferably, after the ball milling or sand milling, the slurry obtained by the ball milling or sand milling is filtered.

[0065] Preferably, the mesh size of the filtration is 60 to 800 mesh, for example 60 mesh, 80 mesh, 100 mesh, 200 mesh, 300 mesh, 400 mesh, 500 mesh, 600 mesh, 700 mesh or 800 mesh, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0066] As a preferred technical solution of the present invention, the spray granulation uses a centrifugal spray device.

[0067] Preferably, the drying temperature of the spray granulation is 150-300°C, for example, 150°C, 180°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0068] Preferably, the feed rate of the spray granulation is 0.5 to 1000 L / h, for example, 0.5 L / h, 0.8 L / h, 1 L / h, 10 L / h, 50 L / h, 100 L / h, 200 L / h, 300 L / h, 400 L / h, 500 L / h, 600 L / h, 700 L / h, 800 L / h, 900 L / h or 1000 L / h, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0069] Preferably, the maximum particle size of the dispersed powder is ≤20μm, for example, it can be 20μm, 18μm, 16μm, 14μm, 12μm, 10μm, 8μm, 6μm, 4μm, 2μm or 1μm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0070] Preferably, the D50 particle size of the dispersed powder is 2 to 15 μm, for example 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0071] As a preferred technical solution of the present invention, the dispersion method comprises the following steps:

[0072] (1) Ingredients: Calculate and weigh each material according to the mass ratio of dispersion coating agent: silicon nanowire: conductive agent (0.1-8): (87-99.8): (0.1-5); Calculate and weigh the solvent according to the solid content of all materials added to the solvent being 0.5-10 wt %;

[0073] The dispersing coating agent includes any one of PVDF, PMMA, PDMS or PI-PA copolymer or a combination of at least two thereof; the conductive agent includes any one of CNTs, VGCF or graphene or a combination of at least two thereof; the silicon nanowire is prepared by VLS method, has a wire diameter of ≤250nm, and is a sponge-like entangled block solid; the solvent includes any one of NMP, DMSO, DMAC, DME, DMF, TCM, TEP or THF or a combination of at least two thereof;

[0074] (2) Dissolving and dispersing the coating agent: Add the solvent into a double planetary vacuum mixer, then add the dispersing coating agent, and stir for 60 to 180 minutes at a vacuum degree of -0.01 to -0.098 MPa and a rotation speed of 1000 to 5000 rpm;

[0075] (3) Dispersing silicon nanowires: adding a conductive agent and silicon nanowires, stirring for 60 to 180 minutes at a vacuum degree of -0.01 to -0.098 MPa and a rotation speed of 1000 to 5000 rpm to obtain a stirred slurry;

[0076] (4) Ball milling or sand milling: Weigh the grinding balls and the obtained stirring slurry in a ratio of (2.5 to 4):1, put them into a ball mill or sand mill tank, and perform ball milling or sand milling for 10 to 90 minutes at a rotation speed of 300 to 1500 rpm to obtain a ball milled or sand milled slurry;

[0077] The grinding balls include zirconium balls, and the grinding balls include grinding balls with diameters of Φ1, Φ3, Φ5, Φ8 and Φ10, and the mass ratio is Φ1:Φ3:Φ5:Φ8:Φ10=(10-30):(20-40):(25-35):(5-15):(3-15);

[0078] (5) Slurry filtration: filtering the obtained ball-milled or sand-milled slurry through a 60-800 mesh stainless steel screen, and separating the ball-milled or sand-milled slurry from the grinding balls to obtain a spray slurry;

[0079] (6) Spray granulation: The obtained spray slurry is spray-dried by a centrifugal spray device at a drying temperature of 150 to 300°C and a feed rate of 0.5 to 1000 L / h to obtain a dispersed powder with a maximum particle size of ≤20 μm and a D50 of 2 to 15 μm.

[0080] In a second aspect, the present invention provides a dispersed powder of silicon nanowires, wherein the dispersed powder is prepared according to the dispersion method described in the first aspect.

[0081] In a third aspect, the present invention provides a use of the dispersed powder of silicon nanowires according to the second aspect in a lithium ion battery.

[0082] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0083] The present invention adopts the method of adding a chemical dispersing coating agent and physically dispersing by high-speed stirring to initially disperse the sponge-like silicon nanowire block into a slurry, and then finely disperses it by further physical dispersion of ball milling or sand milling, and finally obtains silicon nanowire particles with a coating layer and good dispersion by centrifugal spray granulation.

[0084] The present invention uses PVDF, PMMA, PDMS, PI-PA copolymers, etc. as both excellent dispersants and excellent polymer coating agents, which form a complete coating layer on the outside of the silicon nanowires after drying, which can block the intermolecular forces, prevent the formation of liquid bridges, and prevent oxidation and denaturation; the present invention uses CNTs, VGCF, graphene, etc. as conductive agents to prevent electrostatic agglomeration, reduce material impedance, and improve material conductivity;

[0085] The preparation method of the present invention is particularly suitable for silicon nanowires with a wire diameter of ≤250nm and in the form of sponge-like entangled block solids prepared by the VLS method. It can effectively solve the problems of intermolecular force agglomeration, electrostatic force agglomeration and bonding agglomeration in the air between silicon nanowires, and can obtain dispersed powder with excellent dispersion effect, laying a solid foundation for the subsequent processing and application of silicon nanowires. BRIEF DESCRIPTION OF THE DRAWINGS

[0086] Figure 1 is a scanning electron microscope image of the dispersed powder obtained in Example 1;

[0087] Figure 2 1 is a particle size distribution diagram of the ball milling slurry obtained after ball milling in Example 1. DETAILED DESCRIPTION

[0088] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0089] The silicon nanowires used in the following examples and comparative examples are all silicon nanowires prepared by the VLS method, the wire diameter of the primary particles is ≤250 nm, and the silicon nanowires are sponge-like entangled block solids.

[0090] Example 1

[0091] This embodiment provides a method for dispersing silicon nanowires, the method comprising the following steps:

[0092] (1) Ingredients: Calculate and weigh each material according to the mass ratio of dispersion coating agent: silicon nanowires: conductive agent of 4:94:2; calculate and weigh the solvent according to the solid content of all materials added to the solvent of 5wt%; the dispersion coating agent is PVDF; the conductive agent is CNTs; and the solvent is NMP;

[0093] (2) Dissolving and dispersing the coating agent: Add the solvent NMP into a double planetary vacuum mixer, then add the dispersing coating agent PVDF, and stir for 120 min at a vacuum degree of -0.08 MPa and a rotation speed of 3000 rpm;

[0094] (3) Dispersing silicon nanowires: adding conductive carbon nanotubes and silicon nanowires, stirring for 120 min at a vacuum degree of -0.08 MPa and a rotation speed of 3000 rpm to obtain a stirred slurry;

[0095] (4) Ball milling: grinding balls are weighed at a ball-to-material ratio of 3.2:1; the grinding balls include zirconium balls, the grinding balls include grinding balls with diameters of Φ1, Φ3, Φ5, Φ8 and Φ10, and the mass ratio is Φ1:Φ3:Φ5:Φ8:Φ10=15:30:30:10:9, the grinding balls and the obtained stirring slurry are placed in a ball milling jar, and ball milled for 50 minutes at a rotation speed of 1000 rpm to obtain a ball milled slurry;

[0096] (5) Slurry filtration: The obtained ball-milled slurry is filtered through an 80-mesh stainless steel screen to separate the ball-milled slurry from the grinding balls to obtain a spray slurry after ball milling;

[0097] (6) Spray granulation: The obtained spray slurry was spray dried by a centrifugal spray device at a drying temperature of 260°C and a feed rate of 3 L / h to obtain a dispersed powder with a maximum particle size of ≤20 μm and a D50 of 2 to 15 μm.

[0098] Figure 2 This is a particle size distribution diagram of the ball-milled slurry obtained after ball milling in step (4) of Example 1. It can be seen that the ball milling effectively breaks and disperses the silicon nanowires, and the particle size is concentrated between 0.1 and 10 μm.

[0099] Figure 13 is a scanning electron microscope image of the dispersed powder obtained in Example 1. It can be seen from the figure that after the silicon nanowires are dispersed, ball-milled and spray-dried, PVDF forms a coating layer on the surface of the silicon nanowires, becoming irregular spheres or quasi-spheres. There are also some silicon nanowires that remain linear, forming a multi-dimensional three-dimensional powder in which spheres and wires coexist, which is beneficial to the performance of the material properties.

[0100] Example 2

[0101] This embodiment provides a method for dispersing silicon nanowires, the method comprising the following steps:

[0102] (1) Ingredients: Calculate and weigh each material according to the mass ratio of dispersion coating agent: silicon nanowire: conductive agent of 0.1:99.8:0.1; calculate and weigh the solvent according to the solid content of all materials added to the solvent of 10wt%; the dispersion coating agent is PVDF; the conductive agent is CNTs; and the solvent is NMP;

[0103] (2) Dissolving and dispersing the coating agent: Add the solvent into a double planetary vacuum mixer, then add the dispersing coating agent, and stir for 60 min at a vacuum degree of -0.098 MPa and a rotation speed of 1000 rpm;

[0104] (3) Dispersing silicon nanowires: adding a conductive agent and silicon nanowires, stirring for 60 min at a vacuum degree of -0.098 MPa and a rotation speed of 1000 rpm to obtain a stirred slurry;

[0105] (4) Ball milling: Weigh grinding balls at a ball-to-material ratio of 2.5:1; the grinding balls include zirconium balls, and the grinding balls include grinding balls with diameters of Φ1, Φ3, Φ5, Φ8 and Φ10, and the mass ratio is Φ1:Φ3:Φ5:Φ8:Φ10=10:20:25:5:3. Put the grinding balls and the obtained stirring slurry into a ball mill jar, and ball mill for 10 minutes at a rotation speed of 300 rpm to obtain a ball mill slurry;

[0106] (5) Slurry filtration: The obtained ball-milled slurry is filtered through a 60-mesh stainless steel screen to separate the ball-milled slurry from the grinding balls to obtain a ball-milled slurry to obtain a spray slurry;

[0107] (6) Spray granulation: The obtained spray slurry is spray dried by a centrifugal spray device at a drying temperature of 200°C and a feed rate of 0.5 L / h to obtain a dispersed powder with a maximum particle size of ≤20 μm and a D50 of 2 to 15 μm.

[0108] Example 3

[0109] This embodiment provides a method for dispersing silicon nanowires, the method comprising the following steps:

[0110] (1) Ingredients: Calculate and weigh each material according to the mass ratio of dispersion coating agent: silicon nanowires: conductive agent of 8:87:5; calculate and weigh the solvent according to the solid content of all materials added to the solvent of 0.5wt%; the dispersion coating agent is PVDF; the conductive agent is CNTs; and the solvent is NMP;

[0111] (2) Dissolving and dispersing the coating agent: Add the solvent into a double planetary vacuum mixer, then add the dispersing coating agent, and stir for 180 min at a vacuum degree of -0.08 MPa and a rotation speed of 5000 rpm;

[0112] (3) Dispersing silicon nanowires: adding a conductive agent and silicon nanowires, stirring for 180 min at a vacuum degree of -0.01 MPa and a rotation speed of 5000 rpm to obtain a stirred slurry;

[0113] (4) Ball milling: Weigh grinding balls at a ball-to-material ratio of 4:1; the grinding balls include zirconium balls, the grinding balls include grinding balls with diameters of Φ1, Φ3, Φ5, Φ8 and Φ10, and the mass ratio is Φ1:Φ3:Φ5:Φ8:Φ10=30:40:35:15:15, put the grinding balls and the obtained stirring slurry into a ball milling jar, and ball mill for 90 minutes at a rotation speed of 1500 rpm to obtain a ball milled slurry;

[0114] (5) Slurry filtration: The obtained ball-milled slurry is filtered through a 100-mesh stainless steel screen to separate the ball-milled slurry from the grinding balls to obtain a spray slurry after ball milling;

[0115] (6) Spray granulation: The obtained spray slurry was spray dried by a centrifugal spray device at a drying temperature of 300°C and a feed rate of 5 L / h to obtain a dispersed powder with a maximum particle size of ≤20 μm and a D50 of 2 to 15 μm.

[0116] Example 4

[0117] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that in step (1), the mass ratio of the dispersion coating agent, the silicon nanowires, and the conductive agent is adjusted from 4:94:2 to 0.05:97.9:2.05.

[0118] Example 5

[0119] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that in step (1), the mass ratio of the dispersion coating agent, the silicon nanowires, and the conductive agent is adjusted from 4:94:2 to 0.1:97.8:2.1.

[0120] Example 6

[0121] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that the mass ratio of the dispersion coating agent, the silicon nanowires, and the conductive agent is adjusted from 4:94:2 to 2:96:2 in step (1).

[0122] Example 7

[0123] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that the mass ratio of the dispersion coating agent, silicon nanowires, and conductive agent is adjusted from 4:94:2 to 6:92:2 in step (1).

[0124] Example 8

[0125] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that the mass ratio of the dispersion coating agent, silicon nanowires, and conductive agent is adjusted from 4:94:2 to 8:90.1:1.9 in step (1).

[0126] Example 9

[0127] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that in step (1), the mass ratio of the dispersion coating agent, the silicon nanowires, and the conductive agent is adjusted from 4:94:2 to 8.5:89.6:1.9.

[0128] Example 10

[0129] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that in step (1), the mass ratio of the dispersion coating agent, the silicon nanowires, and the conductive agent is adjusted from 4:94:2 to 4.05:95.9:0.05.

[0130] Embodiment 11

[0131] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that the mass ratio of the dispersion coating agent, silicon nanowires, and conductive agent is adjusted from 4:94:2 to 4.1:95.8:0.1 in step (1).

[0132] Example 12

[0133] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that the mass ratio of the dispersion coating agent, silicon nanowires, and conductive agent is adjusted from 4:94:2 to 3.9:92.6:3.5 in step (1).

[0134] Embodiment 13

[0135] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that the mass ratio of the dispersion coating agent, silicon nanowires, and conductive agent is adjusted from 4:94:2 to 3.9:91.1:5 in step (1).

[0136] Embodiment 14

[0137] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that the mass ratio of the dispersion coating agent, silicon nanowires, and conductive agent is adjusted from 4:94:2 to 3.9:90.6:5.5 in step (1).

[0138] Embodiment 15

[0139] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of Embodiment 1 except that the vacuum degree is adjusted from -0.08 MPa to -0.1 MPa in step (2) and step (3).

[0140] Example 16

[0141] This embodiment provides a method for dispersing silicon nanowires. The conditions of the method are exactly the same as those of Embodiment 1, except that the vacuum degree is adjusted from -0.08 MPa to -0.098 MPa in step (2) and step (3).

[0142] Embodiment 17

[0143] This embodiment provides a method for dispersing silicon nanowires. The dispersion method has the same conditions as in Embodiment 1 except that the vacuum degree is adjusted from -0.08 MPa to -0.04 MPa in step (2) and step (3).

[0144] Embodiment 18

[0145] This embodiment provides a method for dispersing silicon nanowires. The conditions of the method are exactly the same as those of Embodiment 1, except that the vacuum degree is adjusted from -0.08 MPa to -0.05 MPa in step (2) and step (3).

[0146] Embodiment 19

[0147] This embodiment provides a method for dispersing silicon nanowires. The dispersion method has the same conditions as in Embodiment 1 except that the vacuum degree is adjusted from -0.08 MPa to -0.01 MPa in step (2) and step (3).

[0148] Embodiment 20

[0149] This embodiment provides a method for dispersing silicon nanowires. The conditions of the dispersion method are exactly the same as those of Embodiment 1, except that the vacuum degree is adjusted from -0.08 MPa to normal pressure, i.e., 0.1 MPa, in steps (2) and (3).

[0150] Embodiment 21

[0151] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of embodiment 1 except that in step (1), the dispersion coating agent is replaced by PI-PA copolymer instead of PVDF, and the solvent is replaced by DMF instead of NMP.

[0152] Embodiment 22

[0153] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is identical to that of embodiment 1 except that in step (1), the dispersion coating agent is replaced by PDMS from PVDF and the solvent is replaced by TCM from NMP.

[0154] Embodiment 23

[0155] This embodiment provides a method for dispersing silicon nanowires. The dispersion method is completely the same as that of Embodiment 1 except that the conductive carbon nanotubes are replaced by graphene in step (1).

[0156] Embodiment 24

[0157] This embodiment provides a method for dispersing silicon nanowires. The conditions of the method are exactly the same as those of Embodiment 1 except that the conductive carbon nanotubes are replaced by VGCF in step (1).

[0158] Comparative Example 1

[0159] This comparative example provides a method for dispersing silicon nanowires, wherein the dispersion method does not use a dispersion coating agent, that is, in step (1), the silicon nanowires and the conductive agent are calculated and weighed at a mass ratio of 97.9:2.1. Apart from this, the other conditions are exactly the same as those in Example 1.

[0160] Comparative Example 2

[0161] This comparative example provides a method for dispersing silicon nanowires, wherein the method does not use a conductive agent. That is, in step (1), the material dispersion coating agent and the silicon nanowires are calculated and weighed at a mass ratio of 4.1:95.8. Apart from this, the other conditions are exactly the same as those in Example 1.

[0162] Comparative Example 3

[0163] This comparative example provides a method for dispersing silicon nanowires. The method does not involve ball milling or sand milling. Steps (5) and (6) are performed directly after step (3). Other conditions are exactly the same as those in Example 1.

[0164] Comparative Example 4

[0165] This comparative example provides a method for dispersing silicon nanowires, wherein the dispersion method does not involve spray granulation. After step (5), the spray slurry is dried normally, then crushed and sieved to control the maximum particle size to be ≤20 nm and the D50 to be 2 to 15 nm. Other conditions are exactly the same as those in Example 1.

[0166] The dispersed powder obtained in the embodiment and the comparative example was pulped and sliced ​​according to the conventional process of button-type lithium battery, assembled into button-type half-cells, and the electrical performance was tested according to the following charge and discharge system:

[0167] (1) Formation: 0.1C (based on the proportion of silicon nanowires, C = 3600 mAh) discharge to 0.01 V, stand for 10 min, 0.1C charge to 1.5 V, stand for 10 min, and cycle 3 times;

[0168] (2) Cycling: Then discharge at 0.2C (based on the proportion of silicon nanowires, C = 3600 mAh) to 0.01 V, leave for 10 min, charge for the first time at 0.1C to 1.5 V, leave for 10 min, and cycle until 80% of the fourth discharge, and calculate the cycle life.

[0169] The results are recorded in Table 1.

[0170] Table 1

[0171]

[0172]

[0173] It can be seen from Table 1 that:

[0174] (1) The data of Examples 1 to 3 show that the dispersed coating agent PVDF has a good coating effect on silicon nanowires, which can effectively improve the initial charge and discharge efficiency of the material and improve the cycle performance of the material; the higher the PVDF ratio, the thicker the PVDF coating on the outside of the material, the greater the material impedance, resulting in a lower charge and discharge capacity of the material; but as the PVDF coating layer becomes thicker, the barrier effect on the electrolyte becomes stronger, and the cycle life of the material increases accordingly.

[0175] (2) The test data of Example 1 and Examples 4 to 9 show that: the more PVDF dispersed coating agent, the better. Too high PVDF content will cause the coating layer to be too thick, which will significantly increase the impedance of the material and thus hinder the material's capacity. The less PVDF, the better. Too little PVDF cannot form a complete coating outside the material particles and cannot effectively block the corrosion of the electrolyte on the material surface, thereby reducing the initial charge and discharge efficiency and shortening the cycle life of the material.

[0176] (3) The test data of Example 1 and Examples 10 to 14 show that: the conductive agent is one of the auxiliary additives, but it will significantly affect the impedance of the material after coating, thereby affecting the capacity and cycle performance of the material; on the other hand, since the conductive agent has a large surface area, it will consume lithium to form an SEI film during the charge and discharge process, thereby affecting the initial charge and discharge efficiency of the material: low conductive agent content will lead to low capacity and poor cycle performance, and high conductive agent content will increase the battery capacity, but at the same time it will reduce the initial charge and discharge efficiency of the battery. A moderate conductive agent content can not only ensure the capacity, but also obtain a suitable initial charge and discharge efficiency, while maintaining a good cycle life.

[0177] (4) The test data of Example 1 and Examples 15 to 20 show that: in the process of initial stirring and dispersing the silicon nanowires, the necessary vacuum degree can not only improve the efficiency and effect of the dispersion, but also prevent the oxidation of the silicon nanowires, thereby ensuring high capacity, high initial efficiency and long life. The lower the vacuum degree, the better the dispersion effect, the lower the degree of oxidation, and the better the performance of the obtained material; under normal pressure or positive pressure, the dispersion effect of the silicon nanowires is poor, the degree of oxidation is high, and the particle size of the obtained material is relatively large, resulting in poor capacity of the material, low initial charge and discharge efficiency, and low cycle life.

[0178] (5) The test data of Example 1 and Examples 17 and 18 show that: the better the mechanical properties of the dispersed coating agent, the stronger the toughness, the better it can resist the volume change of the silicon nanowire material during the charging and discharging process, thereby bringing a better cycle life.

[0179] (6) The test data of Example 1 and Examples 19 and 20 show that the specific surface area of ​​the added conductive agent affects the initial charge and discharge efficiency of the material: the larger the specific surface area, the lower the initial charge and discharge efficiency.

[0180] (7) The test data of Example 1 and Comparative Example 1 show that when there is no PVDF, the capacity utilization, secondary charge and discharge efficiency and cycle life of the material are worse than those of the material with PVDF added.

[0181] (8) The test data of Example 1 and Comparative Example 2 show that when there is no conductive agent CNTs, the capacity utilization, secondary charge and discharge efficiency and cycle life of the material are worse than those of the material with added CNTs.

[0182] (9) The test results of Comparative Examples 3 and 4 show that ball milling and spray drying are both indispensable. Without ball milling or spray drying, products with qualified particle size cannot be obtained, which has a negative impact on the application of the material in subsequent batteries and makes it difficult to produce uniformly dispersed battery slurry.

[0183] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0184] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0185] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0186] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for dispersing silicon nanowires, characterized in that: The dispersion method comprises the following steps: The dispersion coating agent, solvent, silicon nanowires and conductive agent are mixed and crushed, and the crushed slurry is spray-granulated to obtain dispersed powder of silicon nanowires.

2. The dispersion method according to claim 1, characterized in that The dispersion coating agent includes any one of PVDF, PMMA, PDMS or PI-PA copolymer or a combination of at least two thereof; Preferably, the conductive agent comprises any one of CNTs, VGCF or graphene, or a combination of at least two thereof; Preferably, the solvent comprises any one or a combination of at least two of NMP, DMSO, DMAC, DME, DMF, TCM, TEP or THF; Preferably, the silicon nanowires include silicon nanowires prepared using a VLS method; Preferably, the diameter of the silicon nanowire is ≤250nm; Preferably, the silicon nanowires are in the form of a sponge-like entangled bulk solid.

3. The dispersion method according to claim 1 or 2, characterized in that Based on the total mass of the dispersion coating agent, silicon nanowires and conductive agent being 100wt%, the dispersion coating agent accounts for 0.1-8wt%; Preferably, the silicon nanowires account for 87-99.8wt% of the total mass of the dispersion coating agent, silicon nanowires and conductive agent as 100wt%; Preferably, the conductive agent accounts for 0.1 to 5 wt % based on the total mass of the dispersed coating agent, silicon nanowires and conductive agent being 100 wt %; Preferably, after the dispersion coating agent, solvent, silicon nanowires and conductive agent are uniformly mixed, the solid content of the system is 0.5-10 wt %.

4. The dispersion method according to any one of claims 1 to 3, characterized in that: Firstly, the dispersion coating agent and the solvent are mixed evenly, and then the silicon nanowires and the conductive agent are added and stirred evenly; Preferably, the mixing is carried out in a double planetary vacuum mixer; Preferably, the vacuum degree of the mixture is -0.01 to -0.098 MPa; Preferably, the mixing speed is 1000-5000 rpm; Preferably, the mixing time is 60 to 180 minutes.

5. The dispersion method according to claim 4, characterized in that The vacuum degree of the stirring is -0.01 to -0.098 MPa; Preferably, the stirring speed is 1000-5000 rpm; Preferably, the stirring time is 60 to 180 minutes.

6. The dispersion method according to any one of claims 1 to 5, characterized in that: The crushing method includes ball milling or sand milling; Preferably, the ball-to-material ratio of the ball mill or sand mill is (2.5-4):1; Preferably, the grinding balls for ball milling or sand milling include zirconium balls and / or corundum balls; Preferably, the grinding balls of the ball mill or sand mill include at least two diameters; Preferably, the mass ratio of the grinding balls for the ball mill or sand mill is: Φ1:Φ3:Φ5:Φ8:Φ10=(10~30):(20~40):(25~35):(5~15):(3~15); Preferably, the rotation speed of the ball mill or sand mill is 300 to 1500 rpm; Preferably, the ball milling or sand milling time is 10 to 90 minutes; Preferably, after the ball milling or sand milling, the slurry obtained by the ball milling or sand milling is filtered; Preferably, the filtration mesh number is 60 to 800 meshes.

7. The dispersion method according to any one of claims 1 to 6, characterized in that: The spray granulation uses a centrifugal spray device; Preferably, the drying temperature of the spray granulation is 150-300°C; Preferably, the feed rate of the spray granulation is 0.5 to 1000 L / h; Preferably, the maximum particle size of the dispersed powder is ≤20 μm; Preferably, the D50 particle size of the dispersed powder is 2 to 15 μm.

8. The dispersion method according to any one of claims 1 to 7, characterized in that: The dispersion method comprises the following steps: (1) Ingredients: Calculate and weigh each material according to the mass ratio of dispersion coating agent: silicon nanowire: conductive agent (0.1-8): (87-99.8): (0.1-5); Calculate and weigh the solvent according to the solid content of all materials added to the solvent being 0.5-10 wt %; The dispersing coating agent includes any one of PVDF, PMMA, PDMS or PI-PA copolymer or a combination of at least two thereof; the conductive agent includes any one of CNTs, VGCF or graphene or a combination of at least two thereof; the silicon nanowire is prepared by VLS method, has a wire diameter of ≤250nm, and is a sponge-like entangled block solid; the solvent includes any one of NMP, DMSO, DMAC, DME, DMF, TCM, TEP or THF or a combination of at least two thereof; (2) Dissolving and dispersing the coating agent: Add the solvent into a double planetary vacuum mixer, then add the dispersing coating agent, and stir for 60 to 180 minutes at a vacuum degree of -0.01 to 0.098 MPa and a rotation speed of 1000 to 5000 rpm; (3) Dispersing silicon nanowires: adding a conductive agent and silicon nanowires, stirring for 60 to 180 minutes at a vacuum degree of -0.01 to 0.098 MPa and a rotation speed of 1000 to 5000 rpm to obtain a stirred slurry; (4) Ball milling or sand milling: Weigh the grinding balls and the obtained stirring slurry in a ratio of (2.5 to 4):1, put them into a ball mill or sand mill tank, and perform ball milling or sand milling for 10 to 90 minutes at a rotation speed of 300 to 1500 rpm to obtain a ball milled or sand milled slurry; The grinding balls include zirconium balls, and the grinding balls include grinding balls with diameters of Φ1, Φ3, Φ5, Φ8 and Φ10, and the mass ratio is Φ1:Φ3:Φ5:Φ8:Φ10=(10-30):(20-40):(25-35):(5-15):(3-15); (5) Slurry filtration: filtering the obtained ball-milled or sand-milled slurry through a 60-800 mesh stainless steel screen, and separating the ball-milled or sand-milled slurry from the grinding balls to obtain a spray slurry; (6) Spray granulation: The obtained spray slurry is spray-dried by a centrifugal spray device at a drying temperature of 150 to 300°C and a feed rate of 0.5 to 1000 L / h to obtain a dispersed powder with a maximum particle size of ≤20 μm and a D50 of 2 to 15 μm.

9. A dispersed powder of silicon nanowires, characterized in that: The dispersed powder is obtained according to the dispersion method according to any one of claims 1 to 8.

10. Use of the dispersed powder of silicon nanowires according to claim 9 in lithium-ion batteries.